2022
DOI: 10.1111/2041-210x.13958
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance spectroscopy allows rapid, accurate and non‐destructive estimates of functional traits from pressed leaves

Abstract: 1. More than ever, ecologists seek to employ herbarium collections to estimate plant functional traits from the past and across biomes. However, many trait measurements are destructive, which may preclude their use on valuable specimens. Researchers increasingly use reflectance spectroscopy to estimate traits from fresh or ground leaves, and to delimit or identify taxa. Here, we extend this body of work to non-destructive measurements on pressed, intact leaves, like those in herbarium collections.2. Using 618 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 75 publications
0
26
1
Order By: Relevance
“…1390 and 1880 nm; Figs S14–S16). The general pattern of high VIP along the green hump and at the red edge is shared by many traits across studies (Yang et al ., 2016; Ely et al ., 2019; Yan et al ., 2021; Kothari et al ., 2023). In general, visible and red edge reflectance are dominated by pigments and leaf structure (Richardson et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1390 and 1880 nm; Figs S14–S16). The general pattern of high VIP along the green hump and at the red edge is shared by many traits across studies (Yang et al ., 2016; Ely et al ., 2019; Yan et al ., 2021; Kothari et al ., 2023). In general, visible and red edge reflectance are dominated by pigments and leaf structure (Richardson et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The third source is an expanded version of the Dessain dataset previously described in Kothari et al . (2023), which mainly includes sunlit broadleaf trees, shrubs, and herbs from southern Québec and has a large overlap in species with the CABO data. Unlike LOPEX and ANGERS, most of the Dessain trait data were measured using the same protocols as the core CABO datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have often found that leaf chemical traits are estimated better from ground‐leaf spectra than from fresh‐leaf spectra (Couture et al, 2016; Kothari, Beauchamp‐Rioux, Laliberté, et al, 2022; Wang et al, 2020). On some CABO samples, we had also measured spectra after the samples were pressed like herbarium specimens, and again after they were dried and ground (Kothari, Beauchamp‐Rioux, Laliberté, et al, 2022). Among these samples, we again chose no more than ten samples per species ( n = 228; species = 66), and z‐standardized and subsampled bands.…”
Section: Dimensionality Of Spectramentioning
confidence: 99%
“…Curran, 1989) for interpretation. For example, across studies, many traits show high VIP across the green hump and the red edge (Ely et al, 2019; Kothari, Beauchamp‐Rioux, Laliberté, et al, 2022; Yan et al, 2021), which suggests that their estimation may be aided by their covariance with pigment contents or leaf structure. Nevertheless, assigning unambiguous interpretations to these patterns is often challenging because many components' features are shallow and overlapping.…”
Section: Estimating Plant Traits From Spectramentioning
confidence: 99%
See 1 more Smart Citation